Badass Habits : Cultivate the Awareness, Boundaries, And Daily Upgrades You Need to Make Them Stick - Sincero, Jen (United State Penguin Random House, 2023)
New York Times bestselling author Jen Sincero gets to the core of transformation: habits--breaking, making, understanding, and sticking with them like never before.
Keywords: Habits -- Behavior Therapy -- Personal Growth